Pendidikan dan Pelatihan Pembuatan Makanan Sehat dan Bergizi pada Ibu Balita dan Kader Posyandu Bojong Kupa Sukamaju Kaler Kota Tasikmalaya - Rizka Fikrinnisa; Kosasih Adi Saputra; Andik Setiyono (Yayasan Inspirasi El Burhani, 2023)
Introduction: Nutrition is an important factor in the formation of quality, healthy, intelligent and productive human resources (HR). One of the efforts that can be made to improve the nutritional status of toddlers is by holding a supplementary feeding program. Tasikmalaya city is the second higest prevalence in West Java Province. Cases of stunting are still found in the Indihiang Health Center area about 11.18% with most cases of stunting at the Indihiang Health Center were in the Sukamaju Kaler Village, with 103 toddlers. To create a healthy Indonesian society is to empower the community or cadres and mothers who are willing to voluntarily get involved in posyandu issues. Objective: The purpose of this service was to increase nutrition knowledge and equip the skills of mothers and cadres in preparing a healthy supplemenentary food to prevent stunting. Method: This public service was conducted by lectured about nutrition knowledge and demonstrated healthy and nutritious supplementary food for toddler. Result: There was an increase in nutritional knowledge (p = 0.016) and the participants enthusiastically took part in the healthy and nutritious food-making training. Conclusion: Communities empowerment and utilization of local food in research and community service activities can be a nutritional problem solution especially stunting.